A phenomenology of relinquishment as experienced by male adoptees - Quinn, Rose, author (Colorado State University. Libraries, 2008)
The purpose of this dissertation was to gain knowledge about men relinquished and adopted as infants through the stories they tell about themselves. The following research questions were addressed: What are the stories male adoptees are told and then tell others about their relinquishment and adoption? How do they understand their relinquishment? What are the effects of relinquishment and adoption on them and what are the specific times or events in their lives when being relinquished or adopted seem to be more noticeable? Seven men participated in this qualitative phenomenological study. Participants completed a short demographic survey and two personal interviews. All interviews were transcribed and data were analyzed for themes to address the research questions. All participants were told at a very young age they were adopted. Their stories about their relinquishment and adoption came from documents such as letters from birth parents, information from adoptive parents, and conversations with birth mothers. Participants did not express overt negative feelings toward themselves as a result of being adopted. However, they did have many questions about their true identity. Regarding the impact of adoption, the men stated that adoption was just part of their lives; however, it did make them feel their life experience was unique. Participants struggled to find ways to define the term "relinquishment," but all of the participants said that relinquishment was the right decision made by their birth parents and they did not feel "rejected" or "abandoned." Nearly all of the participants mentioned times in their lives when being relinquished/adopted did have an effect on them, such as becoming a parent and reaching the age of their birth parents. The participants had different backgrounds, different ways of being parented, but had similar life stories.
Keywords: adoption; adult; male; men; phenomenological; qualitative; relinquishment; social studies education; developmental psychology; gender studies